Pengaruh Beban Kerja, Konflik Keluarga, dan Kepuasaan Gaji Terhadap Stres Kerja Auditor - Eva Anggra Yunita (Faculty of Economics and Business, University of Pancasakti Tegal, 2018)
This research investigates the causes of work stress among public accountant in public accountant official of Yogyakarta. Specifically, it identifies role overload, family conflict and pay satisfaction. The research constitutes a correlated research with interview and questionnaires. Data for this research was obtained from a 5-points Likert scale questionnaire mailed to 60 public accountant. The statistical method for analysis and hypothesis testing employed in this research was multiple regression based on SPSS program. Results show that there was a positive relationship between workload and work stress. Meanwhile, family conflict and pay satisfaction factor were not related to work stress.